2022
DOI: 10.1186/s13098-022-00801-4
|View full text |Cite
|
Sign up to set email alerts
|

The long-term cost-effectiveness of oral semaglutide versus empagliflozin and dulaglutide in Portugal

Abstract: Background Oral semaglutide is a novel glucagon-like peptide-1 (GLP-1) analog that has been associated with improvements in glycated hemoglobin (HbA1c) and body weight versus sodium-glucose cotransporter-2 inhibitor empagliflozin and injectable GLP-1 receptor agonist dulaglutide in the PIONEER 2 clinical trial and in a recent network meta-analysis (NMA), respectively. The aim of the present study was to evaluate the long-term cost-effectiveness of oral semaglutide 14 mg versus empagliflozin 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(99 reference statements)
0
3
1
Order By: Relevance
“…Studies in multiple countries have also variously found oral or s.c. formulations of semaglutide to be cost-effective compared with medications such as insulin, empagliflozin, liraglutide, and dulaglutide for the treatment of T2D [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in multiple countries have also variously found oral or s.c. formulations of semaglutide to be cost-effective compared with medications such as insulin, empagliflozin, liraglutide, and dulaglutide for the treatment of T2D [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the previously confirmed cost-effectiveness of injectable semaglutide compared to dulaglutide ( Hu et al, 2022a ), our study further demonstrated a clear cost-effectiveness of its oral formulation. Studies in the US and Portugal have also confirmed the cost-effectiveness of oral semaglutide compared with dulaglutide ( Risebrough et al, 2021 ; Malkin et al, 2022 ). Moreover, our model predicted the cost-effectiveness of oral semaglutide compared with liraglutide, with the total incremental QALY (+0.02) consistent with that reported in the literature (0.01–0.07) ( Bain et al, 2020 ; Risebrough et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…From the product-level perspective, semaglutide (oral or injectable) and empagliflozin were the most frequently used main comparators. Oral semaglutide was found to be cost effective in five of seven comparisons with empagliflozin [51,53,58,60,61,63,64] but was not cost effective in two comparisons [58,64]. Injectable semaglutide was found to be cost effective in all comparisons with empagliflozin [49,57,59] except one [59].…”
Section: Glp1 Compared With Sglt2mentioning
confidence: 93%
“…Explicit reasoning for the choice of risk equation was only present in a few cases. Three studies with SGLT2 as the main comparator cited model fit as the reason [40,45,56], while eight GLP1 studies cited advice from model proprietors as the reason [37,38,47,49,57,[61][62][63]. Different aspects of the risk equations were sometimes used simultaneously.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%